The Intertemporal Cross Price Behaviour and the "Fisher Effect" on the Warsaw Stock Exchange - Olbryś, Joanna (Międzyokresowe zależności cen akcji oraz "efekt Fishera" na GPW w Warszawie, 2011)
Market microstructure is now one of the most active research areas in economics and finance. Many authors point to various frictions in the trading process. It has been reported in the literature that some empirical phenomena can be attributed to these frictions. The main goal of this paper is to present the empirical results of testing such phenomena as the "Fisher effect", i.e. positive autocorrelation in market index returns and the intertemporal cross-correlations between pairs of securities' returns on the Warsaw Stock Exchange. According to the author's knowledge, the possible existence of such empirical phenomena in market indexes' returns and securities' returns has not yet been investigated on the WSE.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 153-163
Keywords: struktura rynku; indeks giełdowy; market structure; stock market indexes